Identification of the Intended and Unintended Outcomes of Offering the International Baccalaureate Diploma Program in an International School in Egypt - Belal, Susan Mohamed (ProQuest Dissertations & Theses, 2015)
The purpose of this study is to identify the intended and unintended outcomes of offering the International Baccalaureate Diploma Program (IBDP) at the Cairo American College (CAC) in Egypt, both for the students and the school. This mixed methods study involves a qualitative case study including document analysis, interviews, a focus group, and a quantitative tracer study. The document analysis was performed using literature from within and external to the International Baccalaureate Organization (IBO). At CAC, interviews were conducted with four school administrators, eight students, and ten alumni, while the focus group was conducted with six teachers. Matriculation data for all students graduating from CAC in 2012 and 2013, including those who did not participate in the IBDP, was obtained as part of the tracer study component. The findings of this study show that the outcomes of offering the IBDP at CAC depend on the style of implementation of the IBDP, teacher interpretation of the curriculum, and choices students make during the program. The administrators, teachers, students, and alumni shared intended outcomes which included university preparedness, enhanced writing skills, and perceived advantage for university admissions. The results of the study indicate that offering the IBDP broadened most students' worldviews. It helped students by exposing them to a range of subjects and by developing their research skills. In addition, offering the IBDP helped to attract students to the school. The most frequently stated unintended outcomes of participating in the IBDP were students earning college credit, as well as developing time management and organizational skills. Other unintended outcomes indicated were the stressful and elite nature of the program. Engagement with the diverse local community was not one of the perceived main outcomes of offering the IBDP at CAC and is found to not be unique to participating in the IBDP. The diversity of the CAC student body was perceived as an integral factor for helping students develop a wider worldview. The tracer study results show that three times as many IBDP graduates were enrolled in the top 50 universities worldwide as compared to non-IBDP graduates. The most relevant theoretical frameworks for this study, due to CAC's diverse student body and the mission statement of the IBDP, are Allport's social contact theory and Mezirows' transformative learning theory. These frameworks help understand the IBDP and its impact. The findings of this study inform educators, educational leaders, and the IBO about the intended and unintended outcomes of offering the IBDP at the CAC, including the factors that impact engagement with the diverse local community and international mindedness in the context of the IBDP. There are implications for educational leaders such as the need for a diverse student body in order to help develop wider worldview in students, as indicated by the findings of this study. The findings also reveal several implications for the IBO with respect to the perceived stressful and elitist nature of the IBDP. The IBO should consider the intense workload both for the students and the teachers, as well as the exclusive nature of the IBDP mostly due to the cost. There are also implications for the IBO in that the outcomes of the IBDP are dependent on the school, teacher, and student. This results in variable outcomes for each participating individual student. For example, the outcomes of creativity, action, and service (CAS) are dependent on students' choices of project. In addition, there are implications for educators as they embark on their journey of teaching course content while trying to implement the ideological aims of the IBO.